Development of a reduced chemical mechanism for ammonia/n-heptane blends. (15th April 2023) - Wang, Bowen; Dong, Shijun; Jiang, Zuozhou; Gao, Wenxue; Wang, Zhongxuan; Li, Jianwei; Yang, Can; Wang, Zhaowen; Cheng, Xiaobei
Highlights: A well validated reduced chemical model for ammonia/ n -heptane blends was proposed. The important interaction reactions between ammonia and n -heptane are included. Simulations of the reduced and detailed mechanisms match well at different conditions. Abstract: A reduced chemical mechanism for ammonia/ n -heptane blends, which consists of 495 reactions and 74 species, is proposed in this study. This reduced mechanism is developed using the direct relation graph with error propagation (DRGEP) method based on the latest detailed kinetic mechanism of ammonia/ n -heptane blends, which includes the important interactive reactions between n -heptane and ammonia ( n -C7 H16 + NH2 <=> C7 H15 + NH3 ). The reduced mechanism was first validated against experimental ignition delay times (IDTs) and laminar burning velocities (LBVs) for different ammonia/ n -heptane blends and can capture well these data. Moreover, both the detailed and reduced mechanisms were used to simulate the combustion and emission characteristics of a homogeneous charge compression ignition (HCCI) engine fueled by different ammonia/ n -heptane blends. The simulation results show that the predicted auto-ignition timings and peak pressure values of the reduced mechanism match reasonably well with those of the detailed mechanism for different ammonia/ n -heptane blends. Also, the predicted time-history profiles of the important pollutants, including NO, NO2, N2 O and HCN, show reasonably good agreement between the detailed and reduced mechanisms, and the maximum discrepancy of the peak concentration is within a factor of two. The important reaction pathways of pollutant formations at HCCI engine conditions are discussed in detail. Furthermore, the current reduced mechanism is also used to simulate the combustion process of an ammonia/diesel dual-fuel engine. Overall, the engine combustion phasing, peak pressure, and heat release can be well simulated using the current mechanism, and the computational efficiency is acceptable.